The Relationship Between Work Length and Work Position with the Rate of Low Back Pain among Rice Farmers - Enggal Hadi Kurniyawan; Anisah Febrian Nabila; Grandisya Justitia Purwanto; Nindy Dwi Maharani; Ika Nilasari; Alfid Tri Afandi; Dicky Endrian Kurniawan (JOURNAL OF NONCOMMUNICABLE DISEASES, 2023)
Low back pain (LBP) is defined as pain that appears between the costal margin and inferior gluteal folds for more than one day, which can be accompanied by leg pain or numbness. Often,  this pain is acute and radiates to the buttocks or thighs. LBP is caused by a farmer's poor body position when working, so it can affect performance and results. A working duration that is too long and exceeds the body's capacity can also increase the risk of LBP in farmers. This think about points to decide the relationship between over-the-top work term and non-ergonomic working positions in rice ranchers with lower back pain. The literature search process in this literature review uses three databases: Google Scholar, Scient Direct, and Pubmed, with a publication year range of 2017–2023. The search was carried out using several keywords in English and Indonesian. From all the search results, ten articles match the research criteria and can be continued to the analysis stage. The study's findings found a relationship between work term, work position, and the rate of LBP in farmers.